PRINCIPLES OF NUTRITION IN CANCER MANAGEMENT - Jamdade, Mrunal Ashay (International Journal of Research -GRANTHAALAYAH, 2018)
Now a day number of cancer patients are increasing. There are many reasons for cancer development and eating habits is one of them. Of course, medical field has answer for cancer treatment. But they cause severe nutritional damage to humane body. Proper nutrition care in cancer patient results in patient’s health improvement and cancer recurrence chances are reduced. With help of this nutrition therapy patient can tolerate treatment and damage to body can be minimized. Medical nutrition therapy has promising role in prevention of cancer. This article is a sincerer attempt to highlight importance of nutrition in cancer management.